Studies of the role of steroid hormone in the regulation of oocyte maturation in cattle - Yamashita Yasuhisa; Yamashiro Hideaki; Kumamoto Kanako; Isobe Naoki; Wang Hai; Terada Takato (BMC, 2006)
Abstract Background The objective of this study was to investigate whether the steroid hormone(s) secreted from cumulus-oocyte complexes (COCs) is a prerequisite for bovine oocyte maturation and cumulus expansion using aminoglutethimide (AGT), a P450 cholesterol side-chain cleavage inhibitor. Methods In experiment 1, COCs were cultured in maturation medium with various concentrations of AGT for 22 h to determine the effective concentration of AGT to inhibit steroid hormone secretion, meiotic maturation and cumulus expansion. In experiment 2, COCs were cultured in conditioned medium (CM) and TCM-199 medium with or without 10 mM AGT to check whether steroid hormones secreted from COCs were responsible for oocyte maturation and cumulus expansion. Experiments 3 and 4 were carried out to determine whether exogenous progesterone or estradiol-17beta was able to overcome the inhibitory effects of AGT on oocytes maturation and cumulus expansion. COCs cultured in 10 mM AGT-containing medium supplemented with various concentrations of progesterone or estradiol-17beta for 22 h were examined for oocyte maturation and cumulus expansion. Results Experiment 1 showed that a concentration of 10 mM AGT in medium was sufficient to block steroid hormone secretion, oocyte maturation and cumulus expansion, and that these inhibitory effects were fully reversible. In experiment 2, the addition of 10 mM AGT to CM did not significantly prevent oocyte maturation and cumulus expansion, implying that CM contains the steroid hormone(s) secreted from COCs, which are closely associated with oocyte maturation and cumulus expansion. The results in experiments 3 and 4 demonstrated that the addition of any concentration of progesterone or estradiol-17beta in the medium did not reduce the inhibitory effects of AGT on oocyte maturation and cumulus expansion. Conclusion Our results indicate that bovine oocytes surrounded by cumulus cells are prevented from maturation and cumulus expansion through the inhibition of steroid secretion due to AGT, and that these inhibitory effects of AGT on oocyte maturation and cumulus expansions can not be overcome by the addition of either progesterone or estradiol-17beta in the medium. These observations suggest that some steroid hormone(s) other than P4 and E2 secreted from bovine COCs is essential for their meiotic maturation and cumulus expansion.